Propuesta de Planificación Regional para Recuperar la Reserva Natural de Meremberg (La Plata – Huila) (2020)
The thesis project - Environmental Recovery of the Meremberg Nature Reserve, aims to communicate to the population at a general level, the great ecological and historical potential that this represents for the Municipality of La Plata, and for the Country; The method being sought establishes all the environmental components in the recovery of flora and fauna species, generating tourism and environmental education through urban planning. This project is developed from the recovery of an important ecosystem that is soon to become extinct (Meremberg Nature Reserve), through a land use master plan and a direct relationship with the community of ethnic families and neighboring inhabitants. The study that is proposed in the sector where this ecosystem is geographically located, is aimed at generating solutions, objectives or objectives, through an educational quality in which an urban intervention model is proposed (Urban Regeneration) with all urban operators , through pleasant spaces and the natural landscape.